2007
DOI: 10.2139/ssrn.1522515
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-Sharing in an Online Community of Health-Care Professionals

Abstract: Structured AbstractPurpose -The purposes of this study are twofold: (1) to examine the types of activity that nurses undertake on an online community of practice (APN-l) as well as the types of knowledge that nurses share with one another and (2) to examine the factors that sustain knowledge sharing among the nurses from their local perspectives. Design/methodology/approach -An in-depth case study with mixed methods was adopted to obtain rich and naturalistic data including online observations of the messages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Behaviorally, knowledge withholding and a lack of knowledge sharing may appear quite similar, but the drivers behind KWI and a lack of knowledge sharing are strikingly different. While a lack of knowledge sharing is mainly driven by unfamiliarity with the subject and lack of time [10], knowledge withholding may be caused by a number of different reasons. With this notion in mind, we try to identify antecedents of knowledge withholding from the perspective of effort withholding.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Behaviorally, knowledge withholding and a lack of knowledge sharing may appear quite similar, but the drivers behind KWI and a lack of knowledge sharing are strikingly different. While a lack of knowledge sharing is mainly driven by unfamiliarity with the subject and lack of time [10], knowledge withholding may be caused by a number of different reasons. With this notion in mind, we try to identify antecedents of knowledge withholding from the perspective of effort withholding.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The concept of VCoP was only introduced relatively recently by several researchers including [9], [23], [25], [26].…”
Section: B Vcop Modelmentioning
confidence: 99%
“…In designing an interactive community for professionals, it is necessary to understand how the community will be used and what type of knowledge will be shared. A study conducted in 2007 (Hara & Hew, 2007) investigated why and how nurses used an online community of practise. The study found that nurses' use of the online community arose from a need to ask questions and interact with other nurses that are doing the same job that they do.…”
Section: Gladsupportmentioning
confidence: 99%